Analisis Penerapan Sistem Penggajian dan Personalia di Koperasi Mahasiswa “Almamater” UNM - Nurhalizah Nurhalizah; Devyanti Samada; Igustina Igustina; Nurul Musliha Asmalyani; Prisca Arrang Mangesa; Ahmad Teguh Fachrezi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This research aims to analyze the implementation of the payroll and personnel system at the UNM "Almamater" Student Cooperative and assess the extent to which Standard Operating Procedures (SOP) are implemented in each business unit. The research uses descriptive qualitative methods with data collection techniques through in-depth interviews, SOP documentation and salary slips, as well as literature study as the basis for theoretical analysis. The research results show that the payroll system at KOPMA has worked quite well through a combination of manual and semi-digital methods, supported by the use of fingerprints and treasurer verification. The SOPs for each business unit are prepared in detail and play an important role in ensuring discipline and clarity of employee duties. However, several obstacles were still found, such as manual calculation of pieces, not yet optimal separation of tasks, and minimal digitalization of the system. Apart from that, award programs such as Best Employee and Exemplary Employee have a positive impact on work motivation even though they are not yet supported by formal performance evaluations. Overall, KOPMA’s payroll and personnel system has functioned well but still requires improvement to increase efficiency, accuracy and effectiveness of internal control.